AL QUR'ANIC REVIEW OF THE LGBT PHENOMENON: AN ANALYSIS OF SURAH AL-A'RAF VERSES 80-81 - farhan, fadil; Akbar, Ali (BAMALA Institute, 2024)
This article analyzes the LGBT phenomenon from the perspective of the Qur'an, particularly QS. Al-A'raf: 80-81, through the maqashidi method of interpretation that prioritizes the purpose of sharia (maqasid al-shariah). This study aims to explain the Qur'anic view of homosexual behavior as an act that is contrary to human nature and social morals. The research method uses a contextual approach, referring to the interpretations of classical and contemporary scholars to explore the main purpose of the prohibition of LGBT in Islam. The analysis focuses on three main aspects: (1) Hifz al-Nasl (protection of offspring), where the prohibition aims to preserve the continuity of generations and religious values; (2) Hifz al-Nafs (protection of the soul), which links homosexual practices to health risks such as HIV/AIDS; and (3) Hifz al-'Aql (preservation of the intellect), where this behavior is seen as exceeding the limits of common sense. The article recommends a preventive approach through religious education, moral strengthening, and prevention of promiscuity. In conclusion, the Islamic view of LGBT emphasizes the protection of religious values, health, and public morals, which is in accordance with the maqashidi principle in Islamic sharia.